(untitled) - Barnlund, Dean C. (Belmont (California), 1989)
Explores the general concepts in interpersonal communication and then applies the concepts to the Japanese communicative styles
Keywords: Intercultural communication,Communication,Communication,Interpersonal relations; Social aspects,Social aspects; United states,Japan